The Relationship between Anemia and Labor Induction with Uterine Atony Case in Abdoel Wahab Sjahranie Regional Public Hospital in Samarinda - Siti Masitha; Siti Khotimah; Novia Fransiska Ngo (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Postpartum hemorrhage is one of the primary causes of maternal mortality worldwide, with uterine atony accounting for 70-75% of cases. Anemia is one of the risk factors for pre-labor uterine atony, and labor induction is one of the risk factors during labor. The purpose of this study is to see if there is a link between anemia and labor induction and the occurrence of uterine atony at Abdoel Wahab Sjahranie Samarinda Regional Public Hospital. A case-control study was the method of research used in this investigation. The medical records of postpartum mothers who were admitted to Abdoel Wahab Sjahranie Samarinda Regional Public Hospital between 2018 and 2022 provided the source of the data used in this study. Total sampling was the sample strategy utilized in this investigation. 43 postpartum mothers with uterine atony (case samples) and 43 postpartum mothers without uterine atony (control samples) made up the sample size. The analysis's findings revealed a p-value of 0.000002 for the relationship between anemia and uterine atony case and a p-value of 0.268 for the relationship between labor induction and uterine atony case. The conclusion of this study is that there is a relationship between anemia and uterine atony, while there is no relationship between labor induction and uterine atony.